2022
DOI: 10.3390/md21010018
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Characterization and Immunomodulatory Activity of Fucoidan from Sargassum hemiphyllum

Abstract: Fucoidan is a sulfated algal polyanionic polysaccharide that possesses many biological activities. In this paper, a fucoidan (SHF) polysaccharide was extracted from Sargassum hemiphyllum collected in the South China Sea. The SHF, with a molecular weight of 1166.48 kDa (44.06%, w/w), consisted of glucose (32.68%, w/w), galactose (24.81%, w/w), fucose (20.75%, w/w), xylose (6.98%, w/w), mannose (2.76%, w/w), other neutral monosaccharides, and three uronic acids, including glucuronic acid (5.39%, w/w), mannuronic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 55 publications
0
10
1
Order By: Relevance
“…These two structures can promote the proliferative and immunostimulatory effects of immune cells. 37,38 Interestingly, EPS 7-4 and EPS 8-2 contained higher contents of GlcA compared with most of the reported EPS, which has been shown to be one of the important components influencing the immunoreactivity of polysaccharides. 37 Thus, EPS 7-4 and EPS 8-2 significantly increased the viability of THP-1 cells and their expression of cytokines.…”
Section: ■ Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…These two structures can promote the proliferative and immunostimulatory effects of immune cells. 37,38 Interestingly, EPS 7-4 and EPS 8-2 contained higher contents of GlcA compared with most of the reported EPS, which has been shown to be one of the important components influencing the immunoreactivity of polysaccharides. 37 Thus, EPS 7-4 and EPS 8-2 significantly increased the viability of THP-1 cells and their expression of cytokines.…”
Section: ■ Discussionmentioning
confidence: 85%
“…37,38 Interestingly, EPS 7-4 and EPS 8-2 contained higher contents of GlcA compared with most of the reported EPS, which has been shown to be one of the important components influencing the immunoreactivity of polysaccharides. 37 Thus, EPS 7-4 and EPS 8-2 significantly increased the viability of THP-1 cells and their expression of cytokines. Notably, we found that EPS 7-4 and EPS 8-2 rapidly and efficiently induced innate immunity.…”
Section: ■ Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…The absorption band at 846 cm −1 can be attributed to the equatorial C-O-S bending vibration of the sulfate substituent at the axial C-4 position [ 25 ]. The absorption at 812–827 cm −1 suggests the presence of 2,4-O-disulfated fucose or 6-O-sulfated GalNAc [ 26 ] of the fractions F1, F2 and its depolymerized fragment DF1, DF2, indicating that the sulfation mode did not change significantly. The results showed that the backbone structure of fucoidan was not damaged by oxidation degradation.…”
Section: Resultsmentioning
confidence: 99%
“…Hotchkiss et al (2016) highlighted the significance of carrageenan as a leading seaweed product in the above-mentioned industries and pointed out that carrageenan holds the fourth largest share in the global food texture market, following starches, gelatin, and pectin, based on value. Furthermore, hydrocolloids such as carrageenan are widely nitric oxide synthase at both gene and protein abundance levels (Li et al 2022). Oral administration of a fucoidan isolated from Undaria pinnatifida resulted in remarkable immunomodulatory activities in sarcoma 180 subcutaneous xenograft-bearing mice.…”
Section: Commercial Significance Of Sps Isolated From Red Seaweedmentioning
confidence: 99%